Supersymmetric 3-brane from the extended Goldstone-Maxwell supermultiplet - Kapustnikov, A.; Shcherbakov, A. (Вопросы атомной науки и техники, 2001)
A new gauge supermultiplet of the N=2, D=4 supersymmetry with the complex central charge is proposed. Besides the global N=2, D=4 supersymmetry it possesses the symmetry under the central charge transformations and the special N=2 gauge invariance. It is shown that when one of the supersymmetries is spontaneously broken and the gauge is fixed this multiplet describes the standard action of the supersymmetric 3-brane.